Constitutive Interferon Maintains GBP Expression Required for Release of Bacterial Components Upstream of Pyroptosis and Anti-DNA Responses - Liu, Beiyun C. (Cell Rep, 2018)
Legionella pneumophila elicits caspase-11-driven macrophage pyroptosis through guanylate-binding proteins (GBPs) encoded on chromosome 3. It has been proposed that microbe-driven IFN upregulates GBPs to facilitate pathogen vacuole rupture and bacteriolysis preceding caspase-11 activation. We show here that macrophage death occurred independently of microbial-induced IFN signaling and that GBPs are dispensable for pathogen vacuole rupture. Instead, the host-intrinsic IFN status sustained sufficient GBP expression levels to drive caspase-1 and caspase-11 activation in response to cytosol-exposed bacteria. In addition,endogenous GBP levels were sufficient for the release of DNA from cytosol-exposed bacteria, preceding the cyclic GMP-AMP synthase/stimulator of interferon genes (cGAS/ STING) pathway for Ifnb induction. Mice deficient for chromosome 3 GBPs were unable to mount a rapid IL-1/chemokine (C-X-C motif) ligand 1 (CXCL1) response during Legionella-induced pneumonia, with defective bacterial clearance. Our results show that rapid GBP activity is controlled by host-intrinsic cytokine signaling and that GBP activities precede immune amplification responses, including IFN induction, inflammasome activation, and cell death.